Asymptotic inequalities for the distribution of the time of stay of a semi-Markov process in an expanding set of states - Pogorui A. О. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We establish asymptotic estimates for the behavior of the distribution of the time of the first hit of an infinitely remote level by a semi-Markov process on a semiaxis of integer numbers.